TERRITÓRIO E ETNICIDADE AFROCOLOMBIANAS: dinâmicas de luta em Chocó - Hincapié, Liliana Gracia (2013)
Analysis of the configuration of the local, national and international scenarios which propitiated, for the first time in Colombia, the dialogue between the State and the afro-colombian communities aiming towards the acknowledgement of ethnicity and collective property of these communities' territories. Law n°70/1993, which derived from AT55 of the 1991 Constitution, is analyzed as the result of the processes of organization and fight of the afro-colombian communities of the Pacific, which had as a primary axis the reclaim of their ethnicity and their territories. This dissertation approaches the processes and organizational dynamics of the afro-colombian communities of Chocó, as well as their fight strategies in the dialog with the State. It focuses on the protagonists, afro-colombian leaderships, state officers and intellectuals, as well as the disputes, alliances and conflicts established.